PENERAPAN SLOW DEEP BREATHING TERHADAP NYERI CKR DI IGD RUMAH SAKIT PKU MUHAMMADIYAH GOMBONG - Endah Setianingsih; Putra Agina; Reza Nuurdoni (Jurnal Vokasi Keperawatan (JVK), 2020)
Background: Minor head injury is a nervous system disorder caused by a violent blow or jolt to the head or body. As a consequence of this accident an individual will be losing his awareness signed by headache and pain. One way to overcome it is by giving nursing actions like slow deep breathing therapy.Purpose: getting the effect of slow deep breathing therapy to decrease the pain of minor head injury patient.Metode: this study was a quasi-experimental design with Pretest–posttest design with control group approach. A group of 40 respondents were recruited applying by consecutive sampling technique. The study was conducted between the period of June 25 to July 25 of 2007. The study instrument used a pain scale named NRS (numerical rating scale).Result: Based on the data presented that adult age group of intervention group was 60%, while in control group was 55%. Most of gender category was male, 70% of intervention and 75% of control group respectively.  The result of paired samples t-test exam 1 received value sig.(2-tailed) = 0,000, it means that there was different of mean average of pre-test post-test group. Meanwhile, paired samples t-test exam 2 resulted value sig.(2-tailed) = 0,021 (sig>0,05), it means that there was different of mean average of pre-test post-test group.Conclusion: There was effect of slow deep breathing to decrease the pain of minor head injury patient.